Husband Involvement in Maternal, Neonatal, and Child Health Care among Women who Have a Child Less Than one Year in Gondar City, Northwest Ethiopia, 2021 - Azmeraw Ambachew Kebede; Dereje Nibret Gessesse; Nuhamin Tesfa Tsega; Mastewal Belayneh Aklil; Marta Yimam Abegaz; Tazeb Alemu Anteneh; Nebiyu Solomon Tibebu; Haymanot Nigatu Alemu; Tsion Tadesse Haile; Asmra Tesfahun Seyoum; Agumas Eskezia Tiguh; Ayenew Engida Yismaw; et al. (SAGE Publishing, 2022)
Background Improving maternal, neonatal and child health is one of the major components of Sustainable Development Goal and countries implement different strategies to achieve this goal. In spite of this, maternal, neonatal and child mortality remains a public health burden in the developing countries, including Ethiopia. World Health Organization recommend active involvement of men during pregnancy, child birth and the postpartum period as an effective strategy to improve maternal as well as newborn health. Therefore, this study aimed to assess husband involvement in maternal, neonatal and child health care among women who have child less than one year in Gondar city, northwest Ethiopia. Methods A community-based cross-sectional study was conducted among 870 married women who have a child less than one year in Gondar city. A cluster sampling technique was employed to select study participants. Data were entered into Epi Data version 4.6 and exported to SPSS version 25 for analysis. Multivariable logistic regression was done and adjusted odds ratio with a 95% confidence interval was used to report the association between covariates and the outcome variable. Results Husband involvement in Maternal, Neonatal and Child Health (MNCH) care was 66.2% (95%CI: 63, 69.3). Maternal age (18-25years) and (26-35years), having diploma and above education, husband occupation (government employee), (merchant) and (self-employed), planned pregnancy and cesarean delivery were significantly associated with husband involvement in MNCH care. Conclusion In this study, nearly two thirds (66.2%) of women had husband involvement in MNCH care. Therefore, it is important to improve women's educational attainment and actions should be taken to prevent unplanned pregnancy.